2013
DOI: 10.1016/j.neuroscience.2013.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome characterization by RNA-Seq reveals the involvement of the complement components in noise-traumatized rat cochleae

Abstract: Acoustic trauma, a leading cause of sensorineural hearing loss in adults, induces a complex degenerative process in the cochlea. Although previous investigations have identified multiple stress pathways, a comprehensive analysis of cochlear responses to acoustic injury is still lacking. In the current study, we used the next-generation RNA-sequencing (RNA-seq) technique to sequence the whole transcriptome of the normal and noise-traumatized cochlear sensory epithelia (CSE). CSE tissues were collected from rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 91 publications
(107 reference statements)
4
44
2
Order By: Relevance
“…We had previously reported the transcriptional profile of the rat samples (Patel et al, 2013). In that study, the sequence reads were aligned to rn4 (Rat Genome Sequencing Consortium).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously reported the transcriptional profile of the rat samples (Patel et al, 2013). In that study, the sequence reads were aligned to rn4 (Rat Genome Sequencing Consortium).…”
Section: Resultsmentioning
confidence: 99%
“…The RNA-sequencing analyses were performed to define the expression profile of the cochlear genes using a protocol that has been described in our previous publication (Patel et al, 2013). The total RNAs were extracted from the sensory epithelia using a Qiagen RNeasy Micro or Mini kit (Qiagen GmbH, Hilden, Germany) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used the RNA-seq technique to determine the transcriptome of normal cochlear sensory epithelium and differentially expressed genes after acoustic trauma (Patel et al, 2013b). Our sequencing experiment revealed an average of 176 ± 21 million reads for the normal samples collected from the rat cochlea.…”
Section: Transcriptional Analyses Of Noise-induced Changes In Cochleamentioning
confidence: 99%
“…Studies have identified various stress conditions, including oxidative stress, apoptotic responses, ischemia, and energy exhaustion. In contrast to these pathological responses, molecular analyses have revealed complex signaling transduction involving multiple molecular pathways (Cho et al, 2004; Patel et al, 2013b; Taggart et al, 2001). It is expected that future systematic analyses of the global changes in gene expression will generate a complete data set for understanding the molecular mechanisms of noise-induced cochlear degeneration.…”
Section: What We Learn From the High-throughput Analysesmentioning
confidence: 99%